HITUNGAN MUKA SURUTAN PETA DENGAN METODE TRANSFER DATUM, INTERPOLASI LINIER, DAN INTERPOLASI KUADRAT TERKECIL - , YULI PURWANINGSIH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Indonesia, an archipelago country, needs many bathymetry charts for maritime necessity. It will be not efficient if every making of bathymetry chart build tidal station to determine the chart datum, because it need much times and costs. Therefore, the location which has unknown chart datum is necessary to have method which does not require much times and costs. That methods are linear interpolation, least square interpolation, and transfer datum, so the purpose of this research is to determine which method is appropriate for determining chart datum in location which chart datum is unknown. This research calculated chart datum by linear interpolation, least square interpolation, and transfer datum method for Pondok Dayung and Pabelokan Island station. In this calculation was used chart datum from each tidal station which had known from the calculation of Admiralty method. The calculation of chart datum in Pondok Dayung used chart datum value from Ancol Bende, Muara Tawar, Damar Besar Island, and Pabelokan Island, while the calculation of chart datum in Pabelokan Island used chart datum value from Ancol Bende, Muara Tawar, Damar Besar Island, and Pondok Dayung. The analysis result of this calculation was compared chart datum from the result of linear interpolation, least square interpolation, and transfer datum methods with chart datum from the result of Admiralty method that is considered has true value. The result of this research indicated that the calculation by least square interpolation method has chart datum value which is close to Admiralty method with difference -0,73 cm for Pondok Dayung and -0,61 cm for Pabelokan Island so this method can be used in determination of chart datum in location with unknown chart datum.